The Importance of an Internal Quality Assurance System in Improving the Quality of Education in Madrasahs: Urgensi Sistem Penjaminan Mutu Internal Dalam Meningkatkan Kualitas Pendidikan di Madrasah - Taufik, Imam; Istikomah (Indonesian Journal of Innovation Studies, 2026)
General Background: Islamic madrasahs integrate general and religious education to develop academically competent and morally grounded graduates. Specific Background: However, many madrasahs struggle to attain National Education Standards due to resource limitations, variable learning quality, and insufficient human resource readiness for quality management. Knowledge Gap: Existing literature lacks a synthesized understanding of internal quality management frameworks specifically tailored to Islamic educational institutions. Aims: This study synthesizes literature from 2020 to 2024 using the PRISMA-guided Systematic Literature Review method to evaluate internal quality assurance urgency and underlying management concepts. Results: Findings demonstrate that internal quality assurance facilitates continuous curriculum evaluation, enhances teaching practices, drives professional development, and reinforces institutional accountability. Novelty: The study integrates established quality models—Total Quality Management, the European Foundation for Quality Management, and the Baldrige framework—into a cohesive operational structure for madrasahs. Implications: Implementation of this structured quality system empowers madrasahs to surpass national standards, foster a sustainable quality culture, and prepare students effectively for future societal challenges. Key Findings Highlights Internal quality assurance drives continuous evaluation of curricula and teaching practices to meet national educational standards. Visionary leadership and strategic planning foster a sustainable culture of quality and institutional accountability. Quality management frameworks such as Total Quality Management, EFQM, and Baldrige provide structured approaches for institutional development. Keywords : Internal Quality Assurance System, Education Quality, Madrasah Management, Quality Management Frameworks, Educational Evaluation